2007
DOI: 10.1149/1.2729191
|View full text |Cite
|
Sign up to set email alerts
|

NiO/ZrO2-CeO2 Anodes for Single-Chamber Solid-Oxide Fuel Cells Operating on Methane/Air Mixtures

Abstract: Single-chamber SOFCs have received much attention in recent years due to their simple design and low cost. In this work, we evaluated single-chamber SOFCs that operate in methane/air mixtures at high temperatures (900-1000{degree sign}C). YSZ was used as electrolyte, La0.8Sr0.2MnO3 as cathode, and NiO and NiO/ZrO2-50; 70 or 90 mol% CeO2 composites as anode. ZrO2-CeO2 solid solutions were previously characterized by several techniques and results of their structural and catalytic characterization are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The performance of cerium oxide, mainly related to Ce 4+ /Ce 3+ couples, reduction facility and oxygen mobility properties, has been improved by the addition of transition, alkaline-earth, or rare-earth metals. , The incorporation of those metals into the CeO 2 lattice enhanced its redox properties, oxygen mobility, and thermal stability. Particularly, the doping of CeO 2 with Zr promoted its Ce 4+ /Ce 3+ couples, oxygen storage capacity, thermal resistance, and catalytic activity. CeO 2 −ZrO 2 solid solutions showed better thermodynamic properties than pure CeO 2 , because of their improved redox couples formation and reversible oxygen storage properties. Consequently, Ni/CeO 2 −ZrO 2 solid solutions have exhibited excellent catalytic behavior during methane reforming reactions. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of cerium oxide, mainly related to Ce 4+ /Ce 3+ couples, reduction facility and oxygen mobility properties, has been improved by the addition of transition, alkaline-earth, or rare-earth metals. , The incorporation of those metals into the CeO 2 lattice enhanced its redox properties, oxygen mobility, and thermal stability. Particularly, the doping of CeO 2 with Zr promoted its Ce 4+ /Ce 3+ couples, oxygen storage capacity, thermal resistance, and catalytic activity. CeO 2 −ZrO 2 solid solutions showed better thermodynamic properties than pure CeO 2 , because of their improved redox couples formation and reversible oxygen storage properties. Consequently, Ni/CeO 2 −ZrO 2 solid solutions have exhibited excellent catalytic behavior during methane reforming reactions. …”
Section: Introductionmentioning
confidence: 99%
“…This was attributed to the presence of Zr in the support, which considerably altered the electronic environment of the Ce ions, increasing the concentration of the active sites of the surface. Besides, Ni/Ce 0.9 Zr 0.1 O 2 solid solution has been reported as very promising anode material for hydrogen production from methane partial oxidation, for power generation in solid oxide fuel cells operating at intermediate temperatures. , On the other hand, the relationship between activity and coke formation in Ni/CeO 2 -based catalysts has been also investigated . The authors reported, from samples characterization and methane dry reforming tests, an active role of CeO 2 −ZrO 2 mixed oxides in the gasification of surface coke.…”
Section: Introductionmentioning
confidence: 99%
“…Ceria (CeO 2 )-Zirconia (ZrO 2 ) mixed oxides are important constituents of many catalytic systems [1][2][3]. Likewise, they have mixed ion-electronic conductivity, which make them attractive to be used as electrocatalytic anode materials in Solid Oxide Fuel Cells (SOFCs) [4].…”
Section: Introductionmentioning
confidence: 99%